Suppose and are roots of the equation where are integers and . Then is
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Put x = 2 + 3 in x 2 + p x + 1 and 1 − i in x 2 − 2 x + q .
( ( 2 + 3 ) 2 + p ( 2 + 3 ) + 1 ) ( ( 1 − i ) 2 − 2 ( 1 − i ) + q ) = 0 . After simplifying
( 8 + 4 3 + p ( 2 + 3 ) ) ( q − 2 ) = 0 . Therefore, the two factors are
q − 2 = 0 and ( 8 + 4 3 + p ( 2 + 3 ) ) = 0 . Therefore
q = 2 and p = − 4 . Thus
p + q = − 2 .